2005
DOI: 10.1177/0193945904271446
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Control Interventions for Clinical Outcome Studies

Abstract: In the current research environment the design and management of control groups is becoming more complex. The selection of a control group design is dependent on study goals, presence and quality of existing interventions, urgency of the problem or issue being addressed by the intervention, and factors related to the study site. The purpose of the presentation is to identify various approaches to the design of control groups in experimental studies and to identify their strengths, limitations, and applications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 26 publications
0
41
0
4
Order By: Relevance
“…This model has been termed devised usual care (Barkauskas, Lusk, & Eakin, 2005). In the devised usual care model, a control condition is developed that resembles a typical or standard approach to care.…”
Section: Controls That Involve Comparisons To "Usual Care"mentioning
confidence: 99%
See 1 more Smart Citation
“…This model has been termed devised usual care (Barkauskas, Lusk, & Eakin, 2005). In the devised usual care model, a control condition is developed that resembles a typical or standard approach to care.…”
Section: Controls That Involve Comparisons To "Usual Care"mentioning
confidence: 99%
“…Those who do consent may drop out at a higher rate than those in the treatment group (Barkauskas et al, 2005). The former circumstance could leave the trial with a less than representative sample of people with the target problem, and the latter could cause significant bias in the interpretation of outcomes.…”
Section: Summary and Recommendationsmentioning
confidence: 99%
“…The use of control groups without treatment in clinical research is generally difficult to implement or is even unethical. The use of a control group receiving the usual treatment enables the assessment of an experimental intervention when compared to what patients usually receive over the course of their treatments, not affecting a study’s validity and utility 50 - 51 . In order to advance in knowledge concerning sleep patterns of individuals with HF, it is important to compare a group receiving usual outpatient treatment with a group receiving instructions regarding the management of symptoms and groups receiving PH and SHM.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that randomization to no treatment can be a barrier to recruiting, generate resentful demoralization, and increase dropouts in unblinded trials. [40, 41] However, comparing MBSR only to this active control would result in reduced power and fail to control for maturation or spontaneous improvement in both arms. [42] A standard three-armed trial with both active and passive controls overcomes these limitations, but at a cost of diminished statistical power for the primary comparison of active treatment arms.…”
Section: Trial Design and Methodsmentioning
confidence: 99%